Miejsce państwowego monopolu handlu zagranicznego w założeniach socjalistycznego sposobu produkcji - Najlepszy, Eugeniusz (Wydział Prawa i Administracji UAM, 1969)
The aim of the article is an analysis of the state monopoly of foreign trade in a socialist economy. In first part of the article there is discussed an approach, lasting till now, to an essence and conception of socialist foreign trade monopoly. Until recently in economic literature prevailed the opinion that seems to be based on the assumption that a centralized foreign trade system is the only one possible solution, when the foreign trade is taken over by the state. The monopoly of foreign trade and its monopolistic organization form were then identified as being one and the same. Nevertheless such a position may lead to various misapprehensions. For these reasons rejecting identification of foreign trade monopoly with the far centralization of decisions in external trade the author makes a distinction between a monopolistic organizational structure of foreign trade and the category of the monopoly in foreign trade. On the basis of this distinction an attempt is made to define term of the state monopoly of foreign trade as a situation in which a right to realization foreign trade turnovers has not only the central economic authority, but all socialising sphere of national economy. Under such conditions break a principle of foreign trade monopoly can be follow when leading external trade activités by private enterprises and persons will be admited. In this way understood the concept of the monopoly of foreign trade creates generally conditions of foreign trade monopoly for rational activités on external trade field. In the result within the framework of the state monopoly of foreign trade can be apply a different types of mechanizmus, a different methods of organizations of foreign trade turnovers, then to realize the different forms of this model. In the second part of this article it was shown an attempt of description of the most characteristic of the features of the state monopoly of foreign trade. These features can be derived from the general assumptions of the socialist economy, although different solutions for the foreign trade are possible. The features should define every foreign trade model in a socialist economy. They are as follows: 1. necessity of subordination of foreign trade, first of all to the realization of the physical proportions of the national economic plan, 2. need of control and regulation by the state all of foreign trade turnovers, 3. leading dual form of economic calculation in foreign trade: macroeconomic calculus on central level and microeconomic calculus in enterprises.
The Place of the State Monopoly of Foreign Trade within the Framework of Socialist Production